Red ocean traps - Kim, W. Chan (Harvard Business Review Express, 2017)
Compenting in existing is growing less profitable, so companies must find ways to create new markets. But despite much investment and commitment, companies find it extraoediarily difficult to estrablish new market spaces. Instead, they get caught in read ocean traps. - Forcus on attracting new customers. - Worry less about segmentation. - Understand that market creation is not synonymous with either technological innovation or creative destruction. - Stop forcusing on premium versus low-cost strategies.